Exploring the impact of literacy competencies on student entrepreneurship: The role of outcome-based education curriculum - Hidayat, Muhammad; Mariah, Mariah (Universitas Islam Sultan Agung, 2025)
This study investigates the role of the Outcome-Based Education (OBE) Curriculum as a mediator in shaping the influence of financial, digital, and human literacy on student success in entrepreneurial endeavors. Based on insights from economic education, this research explores how OBE curriculum design can facilitate the development and application of essential literacy skills essential for entrepreneurial success. The study used a mixed methods approach, combining quantitative analysis to measure literacy rates and qualitative examination to understand the nuanced mechanisms by which the OBE curriculum mediates these relationships. The findings of this study indicate that digital literacy and human literacy affect student business ventures either directly or indirectly through the implementation of the OBE curriculum while financial literacy does not affect directly or indirectly through the implementation of the OBE curriculum, this study quantitatively shows student business venture reveal the intricate interplay between OBE curriculum, literacy competencies, and entrepreneurial outcomes, offering valuable insights for education practitioners, policymakers, and stakeholders looking to improve entrepreneurship education.